Aberrant histone modifications in pediatric brain tumors - Hamanishi, Erin T.; Dang, Derek; Venneti, Sriram (Frontiers in Oncology, 2025)
Epigenetic modifications, particularly histone post-translational modifications (PTMs), are central to pediatric brain tumor pathogenesis, impacting chromatin structure, gene expression, and genomic stability. Disruptions in histone PTMs, especially lysine methylation and acetylation, arising due to histone mutations or aberrant enzyme modulation are critical drivers of oncogenesis. Lysine methylation, catalyzed by histone methyltransferases (KMTs), modulates chromatin interactions and gene expression through activation or repression, depending on the methylation state and the specific histone residue. Key enzymes, including histone methyltransferases and demethylases, and associated proteins exemplify the functions of writers, readers, and erasers in maintaining histone modification balance. Similarly, histone acetylation, a dynamic process regulated by histone acetyltransferases (HATs) and histone deacetylases (HDACs), plays a crucial role in pediatric brain tumors. Alterations in these components lead to aberrant gene expression and tumorigenesis. Understanding these disrupted processes offers potential for targeted therapies to rewire oncogenic chromatin states and potentially improve patient outcomes.